Determination of electrical conduction mechanism and optical band gap of a new charge transfer complex: TCNQ-PANT - Yakuphanoğlu, Fahrettin; Arslan, M (Pergamon-Elsevier Science Ltd, 2004)
A new charge-transfer compound PANT-TCNQ (PANT = 9-phenylanthracene, TCNQ = 7,7,8,8-tetracyanoquinodimethane) has been prepared from 7,7,8,8-tetracyanoquinodimethane (TCNQ) and 9-Phenylanthracene in dichloromethane at room temperature. The conductivity of the compound, at room temperature is 2.08 X 10(-9) S cm(-1). The temperature-dependence of electrical conductivity of the PANT-TCNQ compound exhibits a semiconductor behavior. The optical spectra indicate that the compound has a direct band gap (2.46 + 0.15 eV) due to direct transition. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: charge transfer compound; conductivity; optical band gap